2020
DOI: 10.1021/acs.inorgchem.0c02084
|View full text |Cite
|
Sign up to set email alerts
|

Versatility of Amide-Functionalized Co(II) and Ni(II) Coordination Polymers: From Thermochromic-Triggered Structural Transformations to Supercapacitors and Electrocatalysts for Water Splitting

Abstract: The new 2D coordination polymers (CPs) [M(L) 2 (H 2 O) 2 ] n [M = Co II (1) and Ni II (2); L = 4-(pyridin-3-ylcarbamoyl)benzoate] were synthesized from pyridyl amide-functionalized benzoic acid (HL). They were characterized by elemental, Fourier transform infrared, thermogravimetric, powder X-ray diffraction (PXRD), and single-crystal X-ray diffraction (XRD) structural analyses. Single-crystal XRD analysis revealed the presence of a 2D polymeric architecture, and topological analyses disclose a 2,4-connected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 86 publications
(164 reference statements)
3
18
0
Order By: Relevance
“…[107] Even sometimes, Co and Ni metals reacting with similar building blocks could afford the isostructural architectures. [108] Therefore, we put it together to discuss the current trends of Co-and Ni-based MOFs as SCs electrodes in this review (Table 1). [93] Copyright 2014, Elsevier.…”
Section: Co-or Ni-based Mofs As Scs Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…[107] Even sometimes, Co and Ni metals reacting with similar building blocks could afford the isostructural architectures. [108] Therefore, we put it together to discuss the current trends of Co-and Ni-based MOFs as SCs electrodes in this review (Table 1). [93] Copyright 2014, Elsevier.…”
Section: Co-or Ni-based Mofs As Scs Electrodesmentioning
confidence: 99%
“…When these new-emerging MOFs have been documented as SCs electrodes, some have also been reported to achieve good electrochemical results. [108,[127][128][129][130][131]…”
Section: Bdc-or Btc-based Co(ni)-based Mofsmentioning
confidence: 99%
“…25−27 Heat frequently induces the loss of lattice and coordinated solvent molecules, resulting in a structural transformation accompanying with the change in coordination environment. 24,29 Until now, there are many reports on mechanochromic behavior in coordination compounds. The reported mechanochromism generally occurs with a change in luminescent signal because most of them are constructed from 5d elements, such as Pt(II) and Au(I) ions, as well as some 3d 10 elements, such as Cu(I) and Zn(II) ions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Ni­(II) ion is one of the 3d transition metals that have a variety of coordination numbers and geometries, each with its own visible color. , Consequently, it is suitable to use a Ni­(II) center for fabrication of a new multistimuli responsive chromic CP. Vapochromism of some Ni­(II) complexes has been reported. ,, For instance, Baho and colleagues showed that the addition of CH 3 CN vapor can cause a change in coordination modes of nitrate ligands, leading to a shift in d–d bands of a Ni­(II) complex and a change in its color .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation